Comparing law : comparative law as reconstruction of collective commitments - Valcke, Catherine (Cambridge, UK : Cambridge University Press, 2018)
Comparing Law will appeal to all involved in comparative legal research, theorists and practitioners, both seasoned or beginners. This book provides an intellectually and linguistically accessible analytic framework for comparative law, one that serves to both redeem the existing scholarship and offer guidance for future work.
Law -- Legal systems -- Engaging wih legal systems : epistemology -- Delineating legal systems : geography -- Comparing legal systems : methodology.
Includes bibliographical references and index.
Keywords: Comparative law